WALL THICKNESS CALCULATION AND ON-BOTTOM STABILITY ANALYSIS FOR OFFSHORE PIPELINE - SOPYAN, YUSUF
Offshore pipeline system is one of offshore building used as a transport media for oil and gas. The oil and gas transported from well or drilling platform to storage or process terminal through pipeline. As a transport media, the existing of submarine pipeline system is very critical in production process activity, especially in oil and gas industry. Any damage or failure in submarine pipeline system could cause serious effects, such as shutdown in production process, environmental damage and threat of people safety. Because of its serious effects, there are many aspects to be analyzed in submarine pipeline system design. Wall thickness calculation and on-bottom analysis are performed, and also studied the influence of parameters on it. The aim of wall thickness calculation is to get the wall thickness which is safe from internal and external pressure. And the aim of on-bottom stability analysis is to know the pipeline stability under external force, i.e hydrodynamic force presented by buoyancy, drag force and inertia force and to know pipeline stability toward soil bearing capacity on seabed. Nominal wall thickness required for product line from BSU to SPM at Pondok Tengah Field, belong to PT PERTAMINA EP is 0.406 inch and concrete thickness required is 2 inch. Wall thickness is influenced primarily by design pressure, nominal diameter, and pipe material. Otherwise for concrete thickness calculation is influenced primarily by pipe wall thickness, pipe nominal diameter and water depth.